Computed tomography image quality in patients with primary hepatocellular carcinoma: intraindividual comparison of contrast agent concentrations - Peng, Fei; Luo, Chaotian; Ning, Xiaojing; Xiao, Fangyan; Guan, Kaiming; Tang, Cheng; Huang, Fuling; Liang, Junli; Peng, Peng (Frontiers in Medicine, 2024)
Objective: To assess the impact of the different concentrations of iodine contrast agents used on the quality of CT images obtained intraindividually in hepatocellular carcinoma patients.In this retrospective study, data from a cohort of 29 patients diagnosed with primary hepatocellular carcinoma who had undergone two preoperative CT-enhanced examinations within a three-month timeframe were analyzed. Each patient was randomly assigned to receive either a lowconcentration contrast agent (300 mg I/ ml Iohexol) or a high-concentration contrast agent (350 mg I/ ml Iohexol) for the first scan and the alternative contrast agent for the second scan. CT images of different liver regions of each patient were compared between low-and high-concentration scans using their own before-and-after control design. Subjective image quality scores for portal vein images were also assessed.The findings of this study indicate that patients in the high-concentration group presented significantly elevated CT values across various anatomical regions, including the liver parenchyma, abdominal aorta, and hepatic portal vein, in comparison with those in the low-concentration group (p < 0.05). Moreover, the high-concentration group demonstrated superior subjective image ratings (p < 0.05). Nevertheless, there was no statistically significant difference in the CT values observed in liver cancer parenchyma scans at different phases between the two groups (p > 0.05).In summary, the use of a high-concentration iodine contrast agent is efficacious in enhancing the visual clarity of the liver parenchyma, the aorta, and the portal vein in individuals diagnosed with primary hepatocellular carcinoma.